2019
DOI: 10.1002/jat.3922
|View full text |Cite
|
Sign up to set email alerts
|

In utero and lactational exposure to triclocarban: reproductive effects on female rat offspring

Abstract: Triclocarban (TCC) is an antimicrobial compound widely used in personal care products such as soaps, toothpaste, and shampoo. This agent is incompletely removed by wastewater treatment and represents an environmental contaminant. Recent studies have shown that TCC is associated with some endocrine disruptions. The aim of the present study was to evaluate if TCC exposure during critical periods of development (gestation and lactation) could lead to adverse effects on reproductive and behavior parameters of fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Both studies indicated a loss of implantation sites both in the pre-implantation and post-implantation phases. Furthermore, in accordance with the results observed with other substances, the analysis of the insecticide β-cypermethrin (β-CPR) [ 54 ] and the antimicrobial triclocarban (TCC) [ 55 ] showed a reduction of the implantation sites and pre-implantation losses, respectively. Therefore, results showed that the different EDC significantly interfere with embryo implantation; the decrease of the implantation sites, indeed, is related to the increase in dosage and administration time of the different EDC.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Both studies indicated a loss of implantation sites both in the pre-implantation and post-implantation phases. Furthermore, in accordance with the results observed with other substances, the analysis of the insecticide β-cypermethrin (β-CPR) [ 54 ] and the antimicrobial triclocarban (TCC) [ 55 ] showed a reduction of the implantation sites and pre-implantation losses, respectively. Therefore, results showed that the different EDC significantly interfere with embryo implantation; the decrease of the implantation sites, indeed, is related to the increase in dosage and administration time of the different EDC.…”
Section: Resultssupporting
confidence: 68%
“…Six studies analyze other different endocrine disruptors [ 52 , 53 , 54 , 55 , 56 , 57 ]. The use of benzo(a)- pyrene (BaP) led to a significant decrease of implantation sites in the study groups treated with doses of 0.2 and 20 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…In zebrafish, TCC can stimulate the expression of aromatase, increase estrogen levels, and cause abnormal embryonic development and endocrine disruption (Shi et al, 2019). In a recent study (Costa et al, 2020), pregnant Wistar rats exposed to TCC (0.3, 1.5, and 3.0 mg/kg/day) from gestation day 0 to lactation day 21 showed a decrease in estradiol levels in F1 female offspring. Additionally, in the adult TCC 3.0 mg/kg group, progesterone levels decreased, pre-implantation loss increased, and the reduced synthesis of progesterone may interfere with the implantation process.…”
Section: Animal Experimental Researchmentioning
confidence: 98%
“…The early-life exposure may interfere with lipid metabolism as increased fat-pad weights and hepatic triglycerides were observed ( Enright et al, 2017 ) [E]. In another study in rats, in utero and lactational exposure to triclocarban was found to affect the offspring, as observed through an increase in pre-implantation loss potentially related to altered progesterone biosynthesis ( Costa et al, 2020 ) [E].…”
Section: Triclocarban [Seda-13 206]mentioning
confidence: 99%